Reimagining Farming in Bengal’s Changing Ecology: Bridging Science and Community Solutions - Mukhopadhyay, Prama; Puskur, Ranjitha (International Rice Research Institute, 2025)
- In flood-prone Makaltala, erratic monsoons and prolonged waterlogging have left thousands of hectaresof paddy submerged for months. - Farmers, especially women, face severe livelihood losses. - Local innovations like water chestnut cultivation and floating vegetable beds offer temporary relief. - Bridging scientific research with lived realities is critical for long-term resilience.